From 3D printing to 4D printing - Ng, Yong Quan (2016)
This report contains a collection of the various properties of both normal polylactic acid and FLX polylactic acid and their different shape memory effect under various stresses and temperatures. The test pieces used in this report were all printed using a 3D printer in standard dog bone shapes and designed using SolidWork software. The testing includes a normal tensile test and a series of loading and unloading test at different strain percentages in both room temperature and 100⁰C. All the experiments were repeated at least 3 times to provide a fair and consistent result. Before and after each experiment, the test pieces were measured for its change in length. Their shape memory effect were also discovered by placing the test pieces in an oven at a temperature way above its glass transition temperature to find out its shape memory effect. Beside the tensile test, other experiments on FLX polylactic acid such as the usage of TGA machine, DSC machine to find out its changes on physical and chemical changes in properties with increasing temperature and time and the different amount of heat needed to increase the specimen’s temperature respectively. Furthermore, the author also explored FLX polylactic acid’s creeping effect over time and calculated their shape fixity ratio and shape recovery ratio based on the data from the loading and unloading tests. Lastly, this report also includes the possible error faced by the author throughout this year long project.